Mechanical and corrosion characteristics of heat-treated wire arc additive manufactured parts of Inconel ® 625 superalloy - Delfino, Fábio Henrique Silva; Koga, Guilherme Yuuki; F. Cavalcante, Thiago R.; Bon, Douglas; Giarola, Joseane; Shen, Jiajia; Oliveira, Joao Pedro; Lopes, Éder Sócrates Najar; Avila, Julian Arnaldo [UNESP] (Springer Nature, 2024)
Inconel ® 625 alloy (IN625) has been used extensively in aerospace, petrochemical, chemical, and marine applications due to its attractive combination of high tensile strength and excellent corrosion resistance. However, manufacturing components of IN625 is still challenging given the shape complexity and the high associated production costs ascribed to the excess metal removal in subtractive manufacturing techniques. Therefore, wire arc additive manufacturing through the direct energy deposition (DED-WA) technique had a growing interest due to gas metal arc welding with regulated metal deposition (GMAW—RMD™) of IN625. In this work, a computer numerical control (CNC) device was developed to perform the deposition of layers of an ErNiCrMo-3 wire to produce rectangular geometries with external dimensions of 210 × 100 × 60 mm and 10 mm thickness walls. Samples were sectioned and had their microstructural and corrosion resistance assessed. Other samples were heat treated and mechanically and electrochemically tested in two conditions: (i) stress relief (SR) and ii) SR followed by solubilization (SR + S), aiming to mitigate the harmful effects of phases formed during DED-WA or heat treatments, such as δ-phase. Thin-walled components, 210 × 100 × 60 mm, and 10 mm, were successfully fabricated by wire arc additive manufacturing through the direct energy deposition (DED-WA) technique. The as-build conditions presented ultimate tensile strength (716 MPa), large elongation fracture (≥ 35%), and intermediate fracture toughness (> 1.25 mm). The stress relief (SR) heat treatment improved mechanical properties (YS of ~ 450 MPa and UTS of ~ 750 MPa). However, the lowest elongation and fracture toughness (≥ 30% and > 0.5 mm) were presented. On the other hand, the additional solution treatment (SR + S) improved the elongation and fracture toughness (≥ 30% and > 1.5 mm) regarding the AB and SR conditions. The corrosion resistance of all the conditions was higher than the one shown by the wire and comparable to the wrought IN625 alloy at the SR and SR + S conditions.
Keywords: Additive manufacturing; Characterization; Corrosion; Heat treatment; Mechanical behavior; Superalloys